Публічне розміщення акцій банківськими установами на Варшавській фондовій біржі з метою залучення додаткових ресурсів - Лернер, Юрій Ілліч; Куропатенко, Крістіна Дмитрівна; Момот, Едуард Володимирович; Скрипка, Аліна Олегівна (НТУ "ХПІ", 2016)
У статті розглядається механізм здійснення залучення додаткових коштів банківською установою шляхом публічного розміщення акцій на Варшавській фондовій біржі. Розглядаються вимоги до розміщення цінних паперів українськими компаніями на фондових біржах. Аналізуються вимоги до лістингу на Варшавській фондовій біржі. Визначаються основні учасники процесу первинного публічного розміщення акцій. Проводиться аналіз переваг і недоліків проведення ІРО на іноземних біржах.

Due to the fact that the development level of Ukrainian banks and the Ukrainian financial market requires funding sources diversification, equity financing increase, and taking into account that foreign investments is an essential component of further development in current economic transformation and integration into the world economy conditions, in this article the mechanism of finding additional funds with the help of initial public offering on the Warsaw Stock Exchange by the banking institution is analyzed. The requirements for public offering of Ukrainian companies’ securities on the Warsaw Stock Exchange as one of the most attractive stock exchanges for Ukrainian entities in recent years, an done which has created favorable and clear conditions for foreign issuers are considered. Also the Warsaw Stock Exchange listing requirements are described. The main participants of the initial public offering process are characterized. Analysis of the IPO’s advantages and disadvantages are evaluated. Moreover, the key to a successful accomplishment of the initial public offering procedure is determined.
A public shares offering on the Warsaw Stock Exchange by banking institutions in order to attract additional resources
Keywords: емітент; цінні папери; лістинг; IPO; issuer